Supercapacitor based on few-layer MoO3 nanosheets prepared by solvothermal method. (2016) - Wang, Shalong; Dou, Kang; Dong, Yuhang; Zou, Yousheng; Zeng, Haibo
In this work, few-layer orthorhombic MoO3 (α-MoO3 ) nanosheets with high crystallinity were prepared by solvothermal method. The thickness of the prepared MoO3 nanosheets is about 15 nm. The effects of temperature and solvent on the growth and morphology of MoO3 nanosheets were investigated and the results show that temperature ranging from 140 to 180°C has little influence on the morphology and size of MoO3 nanosheets, while the kind of solvent has a great impact on it. The electrochemical performances of the prepared MoO3 nanosheets were studied by cyclic voltammetry and chronopotentiometry. The results show that the specific capacitance of the MoO3 nanosheets depends on the temperature, and the maximum specific capacitance of 136.8 F/g is obtained at 160°C.